Dynamic Simulation and Analysis of Engagement Process for Logarithmic Spiral Bevel Gear Based on Accurate 3D Model. Issue 1 (1st January 2022) - Xiao, Yang; Hou, Shengyu; Dai, Shuling; Xu, Xinfeng; Zhang, Jie
Abstract: Based on the accurate 3D model of logarithmic spiral bevel gear, the operation of spiral cone gear engagement is analyzed and simulated by ANSYS. Through the nonlinear static contact analysis of different positions, the stress change rule and the maximum contact stress is obtained. Compared with the theoretical contact stress strength rule, this paper also analyzes the dynamic operation situation of the gear pairs, obtains the dynamic contact situation rule at different engagement times and different rotating speeds, the influence of the rotating speed on the gear contact characteristics is compared too. The static, dynamic performance and change rules of the gear engagement is obtained, which lay a solid foundation for the further research, design and manufacture of spiral bevel gears.